BUILDING SOCIAL CAPITAL AFTER THE RATIFICATION OF THE JOB CREATION LAW IN THE ECONOMIC FRAMEWORK OF MUTUAL COOPERATION - Faizal, Bhismoadi Tri Wahyu; Nugroho, Zahid Sapto (TRUNOJOYO LAW REVIEW, 2022)
The pros and cons of passing the work copyright law concern all elements of society. Not because it is unreasonable but because the momentum, process and conditions are not right. Even so, there is not any reason why the government immediately passed the work copyright law. So, there must be attitudes and solutions when facing the times and dynamics of the state and nation. Capital "capital" has always been an obstacle in an initial step towards independence. However, as a country that is accustomed to cooperation, there will always be a solution to all of these problems. All this cannot be separated from the synergy between the people, the government and all stakeholders.